2014
DOI: 10.31018/jans.v6i2.489
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterosis for yield, its component traits and some grain quality parameters in rice (Oryza sativa L.)

Abstract: Abstract:The experiment was conducted to estimate combining ability and heterosis for yield, yield attributing traits and few grain quality parameters in rice. The crosses were made among three CMS lines i.e., IR58025A, Pusa6A and IR68897A and seven pollen parents viz., Sarjoo-52, Jaya, Sasyashree, Swetha, HUR 5-2, PR-106 and BPT 5204. Twenty one hybrids were generated in line x tester design. The superior hybrids were identified on the basis of combining ability effect and heterosis. Cross combination IR68897… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
14
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 5 publications
7
14
0
3
Order By: Relevance
“…Significant desirable values of SCA effect were also revealed by Pusa 6A x HUR-JM-59221 and IR-68897A x Pusa Sugandh-2. Priyanka et al (2014) reported IR-58025A and Pusa 6A as poor general combiners, while IR-68897A as good general combiner for kernel breadth before cooking which is in accordance with the present findings. Among the female parents, significant positive estimate of GCA effect for kernel length after cooking was recorded by Pusa 6A and IR-58025A.…”
Section: Combining Ability Effects For Various Quality Traitssupporting
confidence: 82%
See 1 more Smart Citation
“…Significant desirable values of SCA effect were also revealed by Pusa 6A x HUR-JM-59221 and IR-68897A x Pusa Sugandh-2. Priyanka et al (2014) reported IR-58025A and Pusa 6A as poor general combiners, while IR-68897A as good general combiner for kernel breadth before cooking which is in accordance with the present findings. Among the female parents, significant positive estimate of GCA effect for kernel length after cooking was recorded by Pusa 6A and IR-58025A.…”
Section: Combining Ability Effects For Various Quality Traitssupporting
confidence: 82%
“…Amongst the hybrids, IR-68897A x Pusa Sugandh-3 evinced highest significant positive SCA effect, followed by Pusa 6A x Pusa Sugandh-2 and IR-58025A x Pusa 2517-2-51-1. Priyanka et al (2014) reported IR-58025A as good general combiner and IR-68897A as poor general combiner for kernel length before cooking. This supports the findings of the present study.…”
Section: Combining Ability Effects For Various Quality Traitsmentioning
confidence: 99%
“…Nilai heterosis yang dapat dicapai oleh padi hibrida ditentukan oleh kemampuan daya gabung antara galurgalur tetua yang merupakan galur murni (Priyanka et al 2014, Hasan et al 2014. Galur-galur tetua merupakan tanaman hasil persilangan sendiri (selfing) secara terusmenerus.…”
Section: Pendahuluanunclassified
“…Menurut Baker (1978), rasio genetik > 1 mengindikasikan pengaruh aksi gen aditif, sedangkan rasio genetik < 1 menunjukkan pengaruh aksi gen nonaditif. Karakter jumlah anakan produktif, jumlah gabah isi per malai, dan bobot 1.000 butir memiliki rasio genetik > 1, sehingga lebih dipengaruhi oleh aksi gen aditif selaras dengan hasil penelitian Bagheri dan Jelodar (2010) dan Priyanka et al (2014). Pengaruh aksi gen aditif memiliki implikasi adanya seleksi positif sehingga untuk meningkatkan karakter-karakter tersebut maka tetua yang digunakan harus memiliki keunggulan dalam hal jumlah anakan produktif, jumlah gabah isi per malai, dan bobot 1.000 butir.…”
Section: Bahan Dan Metodeunclassified
See 1 more Smart Citation